PTH-121 The Burden Of Poor Nutrition In Chronic Pancreatitis: What Are The Impact Of Behavioural And Socioeconomic Factors?. (9th June 2014) - Paranandi, B; Patel, PS; El-Sayed, GH; Joshi, D; Ghai, A; Koshy, K; Chapman, MH; Pereira, SP; Webster, GJ; Johnson, GJ
Abstract : Introduction: Nutrition centred research in pancreatitis has largely focused on acute pancreatitis. There is limited nutritional data in patients with Chronic Pancreatitis (CP), a condition that predisposes to endocrine and exocrine failure, fat-soluble vitamin deficiency and osteoporosis, which may worsen a patient's quality of life and long-term outcome. We aim to determine the prevalence of malnutrition (using the Malnutrition Universal Screening Tool -MUST), active alcohol consumption and cigarette smoking in patients with CP. Methods: Prospective study of consecutive patients with CP attending a tertiary clinic between October and December 2013. They were invited to participate in a face-to-face questionnaire study. Behavioural and socioeconomic data were collated. Results: A cohort of 86 patients identified were predominantly male (67%), White British (62%), median age 58 years (range 18–90), of socio-economic class (SEC) 8 (21% never worked/long-term unemployed) with educational level (EL) 1 (29% degree or equivalent). Aetiologies included alcohol (29%), idiopathic (25%), autoimmune (22%) and gallstones (11%). The aetiology in 6% was actively under investigation. Median follow up was 27.5 months (range 0 – 151) from index appointment. Active alcohol exposure was noted in 33% (28/86) with excessive amounts (m >21 u, f >14 u/week) in 8% (7/86). The majority of patients (> 70%) with ongoing exposure to alcohol had primary aetiologies other than alcohol. Active cigarette smoking was noted in 34%. MUST scores ≥ 1 were noted in 38% (33/86) conferring "medium to high risk of malnutrition". Multiple linear regression analysis of age, gender, ethnicity, SEC, EL, aetiology, alcohol exposure and smoking did not show any statistically significant variables that predicted MUST score. 27% (9/33) patients "at risk of malnutrition" had been referred to or had been seen by a dietitian within the previous 12 months. The remaining 73% (24/33) "at risk" patients all claimed to have received nil or suboptimal nutritional advice with regards to CP within the previous 24 months. Conclusion: Patients with CP attending our tertiary clinic are at significant risk of malnutrition, which may be under-recognised. Behavioural and socioeconomic factors do not allow reliable prediction of risk of malnutrition to be made, in this cohort. This data emphasises the need for an algorithmic approach to improve recognition of malnutrition in CP and for implementation of specialist dietetic, alcohol liaison and smoking cessation services within the outpatient environment. Disclosure of Interest: None Declared.